X-ray imaging for homeland security. (16th August 2010) - Zentai, George
Since 9/11, there has been a growing interest to improve the security both of air travel and of cargo shipping. Visual inspection is the simplest tool and is very efficient when single objects of small size are to be checked. The complexity of inspection increases when we have large 'boxes' and/or when several objects are packed into a closed space, as in luggage or even in larger volumes like shipping containers or trucks. This paper gives a brief overview of how different X-ray techniques are used for fast checking of small and large objects.